The change in the level of cytokines in blood and synovial fluid in the posttraumatic period of patients with deforming osteoarthrosis as continuous chronic disease - Velichkina, A; Naкhaev V; Yarygin, N; Duzhinskaya, U (Annals of Mechnikov’s Institute, 2020)
The actual problem of the modern approach to the management of patients with traumatic injuries with the purpose of forecasting, prevention and treatment of post-traumatic conditions, is to evaluate in this period, the dynamics of cytokine profile circulating in synovial fluid, and the patterns of their production by mononuclear cells of the victims of this profile. Material and Methods. In accordance with the purpose and objectives of this study 144 patients with post-traumatic arthrosis (with a history of traumas of a various nature) in age from 23 to 64 years (average age 43,2±5,7) were examined. Out of all examined patients men was 63 (43.7 per cent), women - 81 (56,3%). As the control group, 18 relatively healthy people aged from 30 to 57 years (average age 45,5±4,3) were examined. All of the examined person, depending on the stage of post-traumatic arthrosis, (acute and chronic classification) were divided into 4 groups. The 1st group consisted of 48 patients with 1st stage of deforming osteoarthrosis, 2nd - 38 patients with stage 2nd stage of deforming osteoarthrosis, 3-th - 35 patients with 3rd stage of deforming osteoarthrosis, 4th - 23 patients with 4th stage of deforming osteoarthrosis. Investigations were carried out at the time of hospitalization prior medical interventions. During the research the following methods were used: clinical, physical, instrumental, follow-up, radiation (MRI, CT, R-graphy), endoscopic, laboratory. The synovial fluid from the affected knee was received during medical diagnostic puncture. The definition of Pro-inflammatory cytokines: IL-1, IL-6 and TNF-a in the blood serum and synovial fluid of the knee joint performed by ELISA on the immunofermental analyzer Abbott AXSYM" using standard kits ProCon ("Protein contour", St. Petersburg, Russia). Data were processed statistically using Student’s t-test. Results and Discussion. Analysis of the results of determination of IL-1R in the serum of patients DK showed that in all stages of the disease, in addition to IV, the contents of this cytokine exceeded the control values in varying degrees of severity. The highest levels of IL-1R in blood serum was revealed in patients with 1st stage of deforming osteoarthrosis. Then downwards in the following order : in patients with 2nd , 3rd and finally, 4th stage of disease on average, respectively, he was 234,4±12,4; 198,7±16,6; 88,2±6,15 (in all cases p<0.05) and 47.4±4,45 PCG/ml. While the levels of IL-1R in the serum of patients with the 1st stage of the disease was 4.0 times; stage 2 - 3.4 times; the third stage is 1.5 times higher than in control. And only in patients with stage 4 of deforming osteoarthrosis contents IL-1R did not differ from the control. A similar pattern was observed when determining the contents of TNF-a in the serum of patients with deforming osteoarthrosis, and only in contrast to the level of IL-1R in patients with 4th stage of deforming osteoarthrosis contents of TNF-and remained significantly higher than in control. So, the content of TNF-a in patients with of deforming osteoarthrosis of the I, II, III and IV stage of disease on average, respectively, amounted to 330,7±24,5; 210,5±17,3; 123,4±15,3 and 98,5±12,7 PCG/ml (in all cases p<0.05) Conclusion. The results obtained in a comparative study of contents of proinflammatory cytokines (IL-1, IL-6 and TNF-a) in the blood serum and synovial fluid at various stages of deforming osteoarthrosis showed that the determination of the spectrum of cytokines in the hearth of the pathological process, in our opinion, is the most perspective and can be a key marker for early detection of damage and organizations of the active preventive measures of deformation processes in the joints in the early post traumatic period of the accident victims, mainly affecting the lower limbs.